Development of zinc salts of amino acids as a new class of biocompatible nucleating agents for poly(l-lactide). (September 2019) - Wei, Zhiyong; Shao, Shengnan; Sui, Meili; Song, Ping; He, Maomao; Xu, Qiang; Leng, Xuefei; Wang, Yanshai; Li, Yang
Graphical abstract: Highlights: Zinc salts of amino acids were developed as a new class of biocompatible NAs for PLLA. The nucleation mechanism was explained by epitaxial nucleation based on lattice matching. The difference in nucleation ability was attributed to the size and uniformity of NA particles. Zincd -phenylalaninate is a promising NA as bioresource additive of PLLA. Abstract: The slow crystallization speed of poly(l -lactide) (PLLA) during practical processing results in the low degree of crystallinity and thus poor heat resistance of the molded articles, which prevents the wider applications of PLLA. The additive of biocompatible nucleating agents is one of the most effective means to promote the crystallization of PLLA, which synchronously preserves the bio-advantages of PLLA materials for biomedical and food applications. In this work, a series of zinc salts of amino acids, including nine kinds ofl -amino acids and six types ofd - ordl -configuration amino acids, was prepared and evaluated as nucleating agents (NAs) for PLLA. The nucleation effect of NAs was compared in terms of the nonisothermal melt crystallization peak temperature of PLLA with 1 wt% loading of NAs under a cooling rate of 10 °C/min. It was found that the nucleation effect of the zinc salts of amino acids depends on the ligand and its configuration. The nucleation mechanism and the difference of nucleation ability were also discussed and explained. Among these tested NAs, zincd -phenylalaninate (Zn(d -Phe)2 ) is the most effective one, which is comparable to the current outstanding NAs, evidenced by the crystallization peak temperature at 130 °C accompanying with the crystallization enthalpy up to 48 J/g. It is expected that Zn(d -Phe)2 is a promising nucleating agent providing high nucleation activity in injection molding and extrusion processing of PLLA articles.